Pathogenic Actions of Cell Adhesion Molecule 1 in Pulmonary Emphysema and Atopic Dermatitis - Azusa eYoneshige; Man eHagiyama; Mitsugu eFujita; Akihiko eIto (Frontiers in Cell and Developmental Biology, 2015)
Cell adhesion mediated by adhesion molecules is of central importance in the maintenance of tissue homeostasis. Therefore, altered expression of adhesion molecules leads to the development of various tissue disorders involving cell activation, degeneration, and apoptosis. Nevertheless, it still remains unclear what initiates the altered expression of adhesion molecules and how the subsequent pathological cascades proceed. In this regard, cell adhesion molecule 1 (CADM1) is one of the candidates that is involved in the development of pathological lesions; it is an intercellular adhesion molecule that is expressed in various types of cells such as pulmonary cells, neurons, and mast cells. Recent studies have revealed that alterations in the transcriptional or post-transcriptional expressions of CADM1 correlate with the pathogenesis of pulmonary diseases and allergic diseases. In this review, we specifically focus on how CADM1 is involved in the development of pathological lesions in pulmonary emphysema and atopic dermatitis.